MORPHOMETRIC CHARACTERISTICS OF RAT TWISTED INTESTINE WALL IN ADMINISTRATION OF CRYOPRESERVED PLACENTA AGAINST THE BACKGROUND OF ACUTE ASEPTIC INFLAMMATION OF ABDOMINAL CAVITY - Shepitko К.V. (World of Medicine and Biology, 2014)
The experimental study has been carried out on 60 senior male rats. Dynamics of changes of morphometric parameters of total wall thickness, thickness of mucosa, submucosa, muscular and serous coats of twisted intestine has been shown. Morphometric indices of twisted intestine wall do not significantly differ between indices in the intact and control (intraperitoneal introduction of 1 ml saline with further skin incision and wound closure) groups of rodents. Single subcutaneous introduction of cryopreserved placenta against the background of acute aseptic inflammation causes changes of studied morphometric parameters (total wall thickness, thickness of mucosa, submucosa, muscular coats) with their reliable ultimate increase on the 5th day, with partial recovery on the 7th day and full recovery of the parameters on the 10th day of the experiment to the values of intact group. The thickness of serous coat was not significantly thickened during the experiment while comparing between the terms and indices of Group I and Group III.